STRUCTURAL ORGANIZATION OF THE CEREBELLUM OF HUMAN FETUSES OF 11-12 WEEKS OF INTRAUTERINE DEVELOPMENT - Школьніков, В.С.; Залевський, Л.Л. (World of Medicine and Biology, 2016)
The study established micrometrical parameters of the hemispheres and of the worm of cerebellum human fetuses of 11-12 weeks, as well as structural organization, morphometric parameters of the structures of the cerebellum and the morphology of radial glia.
Keywords: cerebellar hemispheres; the worm of the cerebellum; morphometric parameters; fetal development; radial glia